THE EFFECT OF EYE MOVEMENT DESENSITIZATION AND REPROCESSING (EMDR) FOR POST TRAUMATIC STRESS DISORDER (PTSD) - Hery Wibowo (Journal of Holistic and Traditional Medicine, 2017)
Post Traumatic Stress Disorder (PTSD) is a disorder that occurs when a person experiences a traumatic event that reactswith the constant fear, feel helpless and afraid, the symptoms evolve for at least a month.. One possibility therapeutictechniques can help to deal with Post Traumatic Stress Disorder (PTSD) is the method of therapy Eye MovementDesensitization And Reprocessing (EMDR). The purpose of this literature study was to determine the effectiveness oftherapy And Eye Movement Desensitization Reprocessing (EMDR) in reducing the incidence of Post Traumatic StressDisorder (PTSD). The method used in this literature study is to collect and analyze articles - research articles and journals(national and international) related to the effect of therapy And Eye Movement Desensitization Reprocessing (EMDR) forPost Traumatic Stress Disorder (PTSD). Articles obtained from electronic journals from Google Scholar, CochraneDatabase, SAGE Journals, PubMed Central International, Wiley Online Library, PubMed Central Europe, The Lancet,Wolters Kluwer Health, etc., using the keyword And Eye Movement Desensitization Reprocessing (EMDR ) and PostTraumatic Stress Disorder (PTSD). The review of the literature found that article 8 indicates that EMDR therapytherapeutic effect against Post Traumatic Stress Disorder (PTSD). The review of the literature found that article 8 indicatesthat EMDR therapy therapeutic effect against Post Traumatic Stress Disorder (PTSD). So it can be concluded that the EyeMovement Desensitization And Reprocessing (EMDR) effect is more effective in reducing the symptoms of Post TraumaticStress Disorder (PTSD). Eye Movement Desensitization And Reprocessing (EMDR) effect is more effective in reducing thesymptoms of Post Traumatic Stress Disorder (PTSD).